(untitled) (International Journal of Engineering and Computer Science, 2017)
Due to increasing bandwidth demand, network providers are moving towards a crucial milestone in network evolution: the Optical Network. Today, the major technology that is promising to meet this high bandwidth demand of networks is optical networking. The high data rates employed by wavelength division multiplexing optical networks make them most suitable for today’s growing network traffic demands. This paper reviews most of the recent research work on traffic management in WDM optical networks. Various challenges involved with optical networks are also discussed in the paper